The relevance of sustainable development goals (SDGs) in maqāṣid al-sharī‘ah dimensions - Isman, Ainul Fatha; Kaltsum, Ummu (Journal of Islamic Economics Management and Business (JIEMB), 2022)
This article analyzes the relevance of sustainable development goals (SDGs) with the maqāṣid al-sharī‘ah dimension. This study uses a qualitative method with a description analysis approach through a literature study. This study shows that SDGs are relevant to the maqāṣid al-sharī‘ah dimension. The first dimension of ḥifẓ al-dīn has relevance to the SDGs in the aspects of peace, justice, and strong institutions and partnerships for the goals. The ḥifẓ al-nafs dimension has relevance to the SDGs on aspects of good health and well-being, gender equality, clean water and sanitation, affordable and clean energy, sustainable cities and communities, and climate action. Ḥifẓ al-‘aql dimension has relevance to the SDGs in quality education. While the ḥifẓ al-naṣl dimension has relevance to life below water and life on land. The dimensions of ḥifẓ al-māl have relevance to the SDGs in the aspects of no poverty, zero hunger, decent work and economic growth, industry, innovation, and infrastructure, reduced inequalities, and responsible consumption and production. In realizing the SDGs, this research implies that Muslim countries must consider the maqāṣid al-sharī‘ah approach.